Frequency of elemental events of intracellular Ca²⁺ dynamics - Thul, Ruediger; Falcke, Martin (American Physical Society, 2006)
The dynamics of intracellular Ca²⁺ is driven by random events called Ca²⁺ puﬀs, in which Ca²⁺ is liberated from intracellular stores. We show that the emergence of Ca²⁺ puﬀs can be mapped to an escape process. The mean ﬁrst passage times that correspond to the stochastic fraction of puﬀ periods are computed from a novel master equation and two Fokker-Planck equations. Our results demonstrate that the mathematical modeling of Ca²⁺ puﬀs has to account for the discrete character of the Ca²⁺ release sites and does not permit a continuous description of the number of open channels.